Effects of integrated stem approach towards secondary school students’ critical thinking skills and achievement in genetics / Yaki Akawo Angwal - Yaki Akawo , Angwal (2019)
Complex problems in real-life are multidisciplinary. Solving these problems require the ability to think critically and the integration of knowledge from science, technology, engineering, and mathematics (STEM) disciplines. Nevertheless, the observed instructional practices in schools are traditionally-based, and subjects are learnt in isolation which seems not to promote critical thinking skills and academic achievement adequately. Consequently, this study investigated the effects of integrated STEM approach (iSTEMa) on secondary school students’ critical thinking skills and achievement in genetics. The study adopted a concurrent mixed method design: the 2x2 factorial and basic qualitative method. Two schools were chosen randomly and assigned as treatment and control group respectively. In the treatment school, 51 students were randomly selected while 49 students were selected from the control school. An instructional material named iSTEMim was prepared for the treatment group. The iSTEMim consists of six instructional elements, and three tasks. The quantitative data were collected using Science Critical Thinking Test, and Genetic Achievement Test. The qualitative data were collected using interviews and observation. Quantitative data were analysed using Multivariate Analysis of Variance (MANOVA), and the qualitative data were analysed thematically. The findings show that there is a significant difference in students' critical thinking skills between the iSTEMa and traditional group. The difference is in favour of the iSTEMa group, indicating that iSTEMa is more effective. The results also indicated that the iSTEMa group perform better than the traditional group in Genetic Achievement Test. It was also found that students’ ability did not to influence students’ critical thinking skills and genetic achievement. The qualitative data corroborated the quantitative findings. Students were engaged in iSTEMim activities that promoted students’ cognitive processes as well as social interaction. This study has implications for policy-makers to encourage the implementation of integrated STEM approaches in schools. It also has implications for teachers’ instructional practices in the classroom.